Revistas Indexadas - PBCIB, Revista (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2017)
Archeion Online - v. 4, n. 1, n. 2 Ágora - v. 26, n. 53 AtoZ - v. 5, n. 2 Biblionline - v. 12, n. 2, n. 3 Biblioteca Escolar em Revista - v. 5, n. 1 Biblos - v. 30, n. 1, n. 2 BJIS - v. 10, n. 2, n. 3 Ciência da Informação em Revista - v. 3, n. 2, n. 3 Comunicação e Informação - v. 19, n. 2 ETD - v. 18, n. 3, n. 4 Em Questão - v. 22, n. 3 Encontros Bibli - v. 21, n. 46, n. 47 Folha de Rosto - v. 2, n. 1, n. 2, n. esp. InCID - v. 7, n. 2 Informação Arquivística - v. 4, n. 2 Informação & Informação - v. 21, n. 2, n. 3 Informação & Sociedade - v. 26, n. 2, n. 3 Informação @Profissões - v. 5, n. 2 Informação em Pauta - v. 1, n. 1, n. 2 Intexto - n. 35, n. 36, n. 37 Liinc em Revista - v. 12, n. 2 Logeion - v. 3, n. 1 P2P Inovação - v. 3, n. 1 Percursos - v. 17, n. 33, n. 34, n. 35 Perspectivas em CI - v. 21, n. 1, n. 2, n. 3, n. 4 Perspectivas em Gestão e Conhecimento, v. 6, n. 2 Ponto de Acesso - v. 10, n. 2, n. 3 Revista ACB - v. 21, n. 2, n. 3 RACIn - n. esp. RBBD - v. 12, n. 2, n. esp. REBECIN - v. 3, n. 1, n. 2 Revista Conhecimento em Ação - v. 1, n. 2 RDBCI - v. 14, n. 3 RECIIS - v. 10, n. 1, n. 2, n. 3, n. 4 RICI - v. 9, n. 1, n. 2 Senac.DOC - v. 1, n. 1; v. 2, n. 1; v. 3, n. 1 TPBCI - v. 9, n. 1, n. 2 Transinformação - v. 28, n. 1, n. 2, n. 3